Subcorneal pustular dermatosis in a 7-year old Saudi child: A case report and review of the literature - Ali Al Ameer; Abdullah Al Salman; Ibraheem Al Braheem; Yosif Al Marzoq; Mariam Imran (Wolters Kluwer Medknow Publications, 2015)
Subcorneal pustular dermatosis (SCPD) also known as Sneddon-Wilkinson disease (Sneddon and Wilkinson, 1956) is a rare, benign, chronic, sterile pustular eruption which usually develops in middle-age or elderly women; it is rarely seen in childhood and adolescence (Johnson and Cripps, 1974). The primary lesions are pea-sized pustules classically described as half-pustular, half-clear flaccid blisters. Histologically the most important feature is a subcorneal accumulation of neutrophils with the absence of spongiosis or acantholysis. In this paper we present the case of a 7-years-old boy diagnosed with SCPD based on the characteristic clinical and histological features. Oral and topical corticosteroid has been successfully used in the treatment of the disease.